2022
DOI: 10.3389/fpubh.2022.910641
|View full text |Cite
|
Sign up to set email alerts
|

Global, Regional, and National Burden of Cancer in Children Younger Than 5 Years, 1990–2019: Analysis of the Global Burden of Disease Study 2019

Abstract: ObjectivesTo quantify the burden and variation trends of cancers in children under 5 years at the global, regional, and national levels from 1990 to 2019.MethodsEpidemiological data for children under 5 years who were diagnosed with any one childhood cancer were obtained from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) from 1990 to 2019. The outcomes were the absolute numbers and rates of incidence, prevalence, mortality, and disability-adjusted life-years (DALYs) for different types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…According to a Kentucky study, a 20-year database showed the rise from 3.1 in 1995 to 10.3 in 2015 per 100,000 cases of NET patients [ 22 ]. In fact, differences in population rates may result from a combination of environmental factors and biological differences owing to differing national demographics [ 30 , 31 , 32 ]. Ecuador is positioned on the equatorial landline, has territory in both hemispheres, and is traversed from north to south by the Andes Mountains.…”
Section: Discussionmentioning
confidence: 99%
“…According to a Kentucky study, a 20-year database showed the rise from 3.1 in 1995 to 10.3 in 2015 per 100,000 cases of NET patients [ 22 ]. In fact, differences in population rates may result from a combination of environmental factors and biological differences owing to differing national demographics [ 30 , 31 , 32 ]. Ecuador is positioned on the equatorial landline, has territory in both hemispheres, and is traversed from north to south by the Andes Mountains.…”
Section: Discussionmentioning
confidence: 99%
“…Male individuals generally had higher age-standardized DALYs and death rates than female individuals for leukemia attributable to occupational risk-related deaths, possibly because men were the main part of social labor and were more engaged in heavy physical labor, thus, they had more chances to contact toxic and harmful substances. In addition, the burden of leukemia itself is higher in men than in women ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing the global and regional burden of cancer in children 0–4 years old between 1990 and 2019 found that although the decrease in incident and prevalent cases was only 4.6% and 8.3%, respectively, the numbers of deaths and disability-adjusted life-years clearly declined by 47.8% and 47.7%, respectively. 54 These advances in the management of childhood malignancies have significantly increased long-term survival and, concomitantly, the burden of long-term morbidity has raised concern. Approximately 40–50% of childhood cancer survivors develop an endocrine disorder in their lifetime.…”
Section: Cancer In the Paediatric Age Groupmentioning
confidence: 99%